2019
DOI: 10.1111/ncmr.12169
|View full text |Cite
|
Sign up to set email alerts
|

Why are Women Less Likely to Negotiate? The Influence of Expectancy Considerations and Contextual Framing on Gender Differences in the Initiation of Negotiation

Abstract: According to social role theory, women are less likely to initiate negotiations and have lower expectancies about negotiation success because the feminine gender role is inconsistent with the negotiator role. However, gender differences should be amplified in masculine contexts (with even more inconsistency between the negotiator role and the feminine gender role) and reduced in feminine contexts (with more consistency between the negotiator role and the feminine gender role). We showed in Study 1 (N = 1,306 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 52 publications
1
33
1
2
Order By: Relevance
“…In line with the above, Kugler et al (2018) meta-analyzed gender and negotiation initiation studies and concluded that women were somewhat less inclined to initiate negotiation, although this difference was subject to moderators (publication year and situational ambiguity). Reif and colleagues replicated this gender difference and showed that women initiated negotiation less than men in specific negotiation contexts; prominent among those were salary negotiations (Reif et al, 2019(Reif et al, , 2020. Following previous studies, we hypothesized: H1.…”
Section: Literature Reviewmentioning
confidence: 74%
See 2 more Smart Citations
“…In line with the above, Kugler et al (2018) meta-analyzed gender and negotiation initiation studies and concluded that women were somewhat less inclined to initiate negotiation, although this difference was subject to moderators (publication year and situational ambiguity). Reif and colleagues replicated this gender difference and showed that women initiated negotiation less than men in specific negotiation contexts; prominent among those were salary negotiations (Reif et al, 2019(Reif et al, , 2020. Following previous studies, we hypothesized: H1.…”
Section: Literature Reviewmentioning
confidence: 74%
“…ambitious, assertive, competitive) (Eagly, 1987;Eagly and Wood, 2012). In negotiation situations, a self-advocating male negotiator is therefore within his gender role, while a self-advocating female negotiator violates her gender role (Bowles et al, 2019;Kugler et al, 2018;Nelson et al, 2015;Reif et al, 2019Reif et al, , 2020Williams and Tiedens, 2016). Accordingly, female, but not male, negotiators, face social backlash.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Sedangkan negosiator pria berdasarkan kepribadiannya yang kompetitif akan lebih tinggi tingkat inisiasinya dalam kontek negosiasi perusahaan publik, kompensasi, sewa, pekerjaan, dan sebagainya. Reif et al, (2020) melanjutkan penelitian mereka tentang perbedaan negosiator berdasarkan perbedaan gender, dan penjelasan yang sama bahwa negosiator pria memiliki tingkat inisiasi yang tinggi dalam bernegosiasi dibandingkan negosiator wanita. Tambahan penjelasannya ialah bahwa perbedaan inisiasi dalam negosiasi tersebut juga dipengaruhi oleh faktor perbedaan harapan.…”
Section: Perbedaanunclassified
“…Vroom’s (1964) VIE theory has three main constructs: valence, instrumentality, and expectancy (for a helpful illustration, see Karau & Williams, 1993). 1 The theory can explain people's intentions and has already been used in research on negotiation and gender (e.g., Reif et al, 2020; Reif et al, 2019). In VIE theory (Vroom, 1964), the technical term expectancy denotes the perceived likelihood with which an effort, or “e,” would lead to a performance, or “p”—thus, expectancy captures the perceived relationship of “e → p” (Van Eerde & Thierry, 1996).…”
Section: How To Attenuate the Implementation Gap?mentioning
confidence: 99%